Enzymatic Degradation of Biofilm by Metalloprotease From Microbacterium sp. SKS10 - Saggu, Sandeep Kaur; Jha, Gopaljee; Mishra, Prakash Chandra (Frontiers in Bioengineering and Biotechnology, 2019)
Enzymes have replaced or decreased usage of toxic chemicals for industrial and medical applications leading towards sustainable chemistry. In this study, we report purification and characterization of a biofilm degrading protease secreted by Microbacterium sp. SKS10. The protease was identified as a metalloprotease, Peptidase M16 using mass spectrometry. It showed optimum activity at 60 °C, pH 12 and retained its activity in the presence of various salts and organic solvents. The enzyme was able to degrade biofilms efficiently at enzyme concentration lower than other known enzymes such as papain, trypsin and ɑ-amylase. The presence of this protease increased the accessibility of antibiotics inside the biofilm, and was found to be non-cytotoxic towards human epidermoid carcinoma cells (A431) at the effective concentration for biofilm degradation. Thus, this protease may serve as an effective tool for management of biofilms.